1933
DOI: 10.2307/1414285
|View full text |Cite
|
Sign up to set email alerts
|

Motor Factors in Voluntary Control of Cube Perspective Fluctuations and Retinal Rivalry Fluctuations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The second subjective control measure was based on four 60-sec trials of which two instructed right-eye-dominant and two ins tructed left-eye-dominant trials were presented in balanced order. From the accumulated time in which the instructed eye pattern was, in fact, dominant (dominant time) and from the time in which it was suppressed (nondominant time), a measure of rivalry dominance control, similar to that used by Washburn and Gillette (1933), could be calculated with the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…The second subjective control measure was based on four 60-sec trials of which two instructed right-eye-dominant and two ins tructed left-eye-dominant trials were presented in balanced order. From the accumulated time in which the instructed eye pattern was, in fact, dominant (dominant time) and from the time in which it was suppressed (nondominant time), a measure of rivalry dominance control, similar to that used by Washburn and Gillette (1933), could be calculated with the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…Figure reversal was believed to be due to the saturation of cortical neurons (Koehler & Wallach, 1944), but it is now clear that the phenomenon has much more complex determinants. For instance, it has been demonstrated that the subjective occurrence of figure reversal depends largely on being informed of its possibility (Girgus, Rock, & Egatz, 1977), that the frequency of the reversal process is a direct function of the ambiguity of the design (Riani, Tuccio, Borsellino, Radilova, & Radil, 1986), and that the reversal process is subject to conscious control (Liebert & Burk, 1985;Pelton & Solley, 1968;Washburn & Gillette, 1932).…”
mentioning
confidence: 99%
“…It has been recognized for a considerable time that binocular rivalry can be affected by voluntary control (Helmholtz, 1925;Breese, 1901;McDougall, 1903;Washburn & Gillette, 1933;George, 1936).The extent of voluntary control may be measured by instructing the S to decrease or increase the rate of alternation for a given test period. A comparison of the rate under the "decrease" instructions with the rate under the "increase" instructions provides a measure of control.…”
mentioning
confidence: 99%
“…It has been recognized for a considerable time that binocular rivalry can be affected by voluntary control (Helmholtz, 1925;Breese, 1901;McDougall, 1903;Washburn & Gillette, 1933;George, 1936).…”
mentioning
confidence: 99%